Coronavirus 2019: a review of virology, clinical features, diagnosis, and treatment - Younus, Shifa; Maqsood, Hamza; Gulraiz, Azouba (International Journal of Research in Medical Sciences, 2020)
Coronavirus 2019 (COVID-19) is an enveloped ribonucleic acid (RNA) virus that is diversely found in humans and wildlife. A total of six species have been identified to cause disease in humans. The most recent outbreak initially presented as pneumonia of unknown etiology in a cluster of patients in Wuhan, China. The epicenter of infection was linked to seafood and exotic animal wholesale markets in the city. SARS-CoV-2 is highly contagious and is a declared global pandemic. This review will introduce a general overview of virology and describe the clinical features, diagnostic testing, and management of COVID-19 patients. There are multiple drug trials going on with some positive results. However, since no vaccine is available, the best way to combat the virus is by preventive methods. Our review will also provide a means to raise awareness among primary and secondary healthcare providers during the current pandemic.